HOW CAN TPACK SUPPORT THE STATISTICAL LITERACY SKILLS OF MATHEMATICS STUDENTS’ TEACHERS? - Rahma Siska Utari; Lis Amalia; Rohman Rohman (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The development of ICT in the industrial revolution 4.0 was very fast and unlimited, causing the importance of statistical literacy for mathematics students’ teachers as global citizens, and future mathematics teacher candidates to be able to interpret and criticize information before communicating it in various media. This study described Technological Pedagogical Content Knowledge (TPACK) in supporting the statistical literacy skills of mathematics students’ teachers. The method used in this research was a design research type validation study to support students' statistical literacy skills by implementing TPACK. Fourteen students who took the Basic Statistics course participated as subjects in this study. Three stages were carried out in this study, namely: the preliminary design, teaching experiment, and retrospective analysis to develop a learning trajectory through learning activities that had been designed through the Hypothetical Learning Trajectory (HLT). Data were collected using observations, interviews, video recordings, statistical project assignments, and tests. Data were analyzed and conclusions were drawn. The results of this study were a series of learning activities that are integrated with TPACK and can be used to support the statistical literacy skills of mathematics students’ teachers including activities: data awareness, statistical conceptual and idea, data presentation, and data representation. Local Instructional Theory (LIT) produced was useful in learning basic statistics to support the statistical literacy skills of mathematics students’ teachers.